PARACRISIS AND SOCIAL MEDIA: A SOCIAL NETWORK ANALYSIS OF HASHTAG #UNINSTALLBUKALAPAK ON TWITTER - Damayanti, Acniah (Universitas Muhammadiyah Yogyakarta, 2020)
Social media has become a double-edged sword for crisis management. It poses both opportunities and challenges. One of the challenges is that social media themselves could risk the organization by generating crisis-threat and amplify it. This crisis-threat is termed as paracrisis, and #uninstallbukalapak is an example of paracrisis. The Twitter public created this hashtag as a response to Achmad Zaky?s, the CEO, tweet that allegedly criticized the incumbent presidential candidate. Using the exploratory Social Network Analysis method, this research investigated the formation of #uninstallbukalapak paracrisis by identifying the most influential actors in the network discussion of #uninstallbukalapak on Twitter and investigated what topics were in the discussion. This research found that the most influential actors in the network of #uninstallbukalapak were @achmadzaky, @bukalapak, and @jokowi. Topics mainly discussed were mistake attribution to Achmad Zaky, the association of #uninstallbukalapak hashtag with presidential candidate support, and also the expression of public support to Achmad Zaky and Bukalapak.